2017
DOI: 10.3386/w23859
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Accountability Incentives in Early Childhood Education

Abstract: In an effort to enhance the quality of early childhood education (ECE) at scale, nearly all U.S. states have recently adopted Quality Rating and Improvement Systems (QRIS). These accountability systems give providers and parents information about program quality and create both reputational and financial incentives for program improvement. However, we know little about whether these accountability reforms operate as theorized. This study provides the first empirical evidence on this question using data from No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…These data were selected because the ECLS-K: 1998 Cohort is one of the few contemporary national data sets that has tracked children’s experiences through early adolescence, which were required to address the study objectives. Even so, recent studies have found that the patterns documented in the 1998 cohort of the ECLS-K closely resemble those of the 2010 cohort through the end of first grade (Bassok et al, 2015), suggesting that the findings documented herein are still relevant today. However, this limitation speaks to a larger issue in a field where cohort effects are of increasing importance for consideration given the changing landscape of early childhood education and, ultimately, because government initiatives may dramatically change this landscape in the coming decades.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These data were selected because the ECLS-K: 1998 Cohort is one of the few contemporary national data sets that has tracked children’s experiences through early adolescence, which were required to address the study objectives. Even so, recent studies have found that the patterns documented in the 1998 cohort of the ECLS-K closely resemble those of the 2010 cohort through the end of first grade (Bassok et al, 2015), suggesting that the findings documented herein are still relevant today. However, this limitation speaks to a larger issue in a field where cohort effects are of increasing importance for consideration given the changing landscape of early childhood education and, ultimately, because government initiatives may dramatically change this landscape in the coming decades.…”
Section: Discussionmentioning
confidence: 56%
“…For the purposes of this investigation, I restricted the sample to children who (a) were first time kindergartners ( n = 16,752) and (b) had valid kindergarten data and preschool information ( n = 16,637). Similar to prior publications with the ECLS-K (see also: Bassok et al, 2015; Curenton et al, 2015; Loeb et al, 2007; Magnuson et al, 2004) and other early childhood evaluations (see also Lee, Zhai, Brooks-Gunn, Han, & Waldfogel, 2014), Head Start was removed from the preschool category for three reasons: (a) it is widely regarded as different than standard center-based care or state-funded pre-K; (b) prior studies have shown that there are no added benefits of Head Start participation in the ECLS-K as compared with parental care (Curenton et al, 2015; Magnuson et al, 2007); and (c) it was not possible to achieve optimal balance across the Head Start and preschool conditions when using propensity score matching, even within the low-income sample (see also: Magnuson et al, 2007). The above exclusion criteria resulted in a final analytic sample of 15,070 children and families.…”
Section: Methodsmentioning
confidence: 56%
“…We also hypothesized that an increased focus on literacy and math would crowd out time spent on other subjects, such as art, music, science, social studies, and physical education (PE). At the same time, we note that over the period we investigated, the percentage of children enrolled in full-day kindergarten rose from 56% to 80% (Bassok, Gibbs, & Latham, 2015). Given this striking increase in the typical number of hours kindergarteners spend in school, another plausible hypothesis would be an across-the-board increase in time devoted to all subjects.…”
Section: The Changing Nature Of Kindergartenmentioning
confidence: 69%
“…In contrast, others have found that the long-term benefits of early education programs are not conditional on the quality of children’s later schooling and, ultimately, the benefits of these programs diminish to a similar degree for all children as they progress through elementary schooling. For example, Bassok, Gibbs, and Latham (2015) found no interaction between preschool experiences and kindergarten-year quality measures, including class size, peer preschool experience, full-day kindergarten, and an index for quality.…”
Section: Sustaining Environmentsmentioning
confidence: 91%